PROBLEMATICS OF REQUIRED LIBERATION OF FOREIGN CITIZENS AND ITS SUPERVISORY MECHANISMS - Rasona Sunara Akbar (Jurnal Ilmiah Kajian Keimigrasian, 2018)
Indonesia is a country that places law as the only rule to play in society, nation and state. To limit freedom which is a human right, legal rules arise which aim to regulate public order, one of which is criminal law, which is a sanction law. Prison sentences in Indonesia, better known as correctional services, are one of the sanctions that aim to create a sense of suffering for the convicted person for losing freedom of movement, guiding convicts to repentance, educating him to become a useful member of Indonesian socialist society. One of the products of Corrections in realizing this is through parole, which is not only valid for Indonesian citizens but also for foreign nationals. Immigration as a state apparatus that handles foreigners both related to traffic and its supervision while in the Indonesian territory cannot be separated from the issue of parole for foreign inmates, especially in matters of residence permit and supervision. The author concludes that the mechanism for the implementation of Conditional Exemption and its supervision for foreign nationals is still considered ineffective because it is not in accordance with the principle of selective policy. In addition, the coordination carried out between Immigration and Correctional Services in the provision of parole to foreigners is only limited to fulfilling the conditions for the provision of parole for foreign citizens (administrative), but regarding the implementation of supervision there is no clear coordination where each institution only runs individual duties and functions.